APOE ε4 alters docosahexaenoic acid's influence on preclinical markers of Alzheimer disease. (December 2021) - Coughlan, Gillian; Larsen, Ryan; Kim, Min; White, David; Gillings, Rachel; Irvine, Michael; Scholey, Andrew; Cohen, Neal; Legido‐Quigley, Cristina; Hornberger, Michael; Minihane, Anne‐Maire
Abstract: Background: Docosahexaenoic acid (DHA) is the main long chain omega‐3 polyunsaturated fatty acids in the brain and accounts for 30% to 40% of fatty acids in the grey matter of the human cortex. Although the influence of circulating DHA levels on memory function is widely researched, its association with brain volumes is under investigated and its association with spatial navigation is virtually unknown. This is despite the fact that spatial navigation deficits are a new cognitive fingerprint for symptomatic and asymptomatic AD, and that spatial navigation crucially relies on hippocampal and the entorhinal cortex integrity. Thus, we investigated the relationship between DHA levels and the major structural and cognitive markers of preclinical AD, namely hippocampal volume, entorhinal volume, and spatial navigation ability, across two independent non‐demented populations. Method: Fifty‐three cognitively normal adults underwent volumetric magnetic resonance imaging, measurements of serum DHA (including serum lysophosphatidylcholine DHA) and APOE ε4 genotyping. Relative regional brain volumes were calculated and linear regression models were fitted to examine DHA associations with brain volume. After testing interactions between DHA and APOE ε4 on brain volume, we investigated whether DHA and APOE interact to predict spatial navigation performance on a novel virtual reality diagnostic test for AD in an independent population of APOE genotyped adults (n = 46). We hypothesized that higher DHA levels would be associated with preserved brain volume and better spatial navigation performance in APOE ε4 non‐carriers but not in APOE ε4 carriers. Result: APOE genotype modulated serum free DHA associations with entorhinal cortex volume and hippocampal volume, both key nodes of the human spatial navigation network. Linear models showed that greater circulating DHA was associated with increased entorhinal cortex volume, but not hippocampal volume, in APOΕ ε4 non‐carriers. APOE also interacted with serum lysophosphatidylcholine DHA to predict hippocampal volume. Crucially, the APOE genotype modulated DHA associations with spatial navigation performance, showing that DHA was inversely associated with path integration in APOE ε4 carriers only. Conclusion: Interventions aiming to increase DHA status to protect against cognitive decline must consider APOE ε4 carrier status.